The quality of sleep: evaluation among university students - Angelillo, Silvia; Sansone, Vincenza; Paduano, Giovanna; Lateano, Ludovica; Di Giuseppe, Gabriella; Nobile, Carmelo Giuseppe Angelo (Frontiers in Public Health, 2024)
Introduction: This study explored the quality of sleep among university students in the South of Italy during the Covid-19 pandemic.Methods: A cross-sectional study was conducted between March 2022 and January 2023 and involved students over the age of 18, who were invited to complete a self-administered questionnaire using an online application.Results: Overall, 88% of men and 94.5% of women had Pittsburgh Sleep Quality Index (PSQI) scores of ≥ 5 and a mean PSQI score of 9.2±3. Students with severe or extremely depression score, with sever or extremely stress score, male and who did not had Covid-19 infection were more likely to have a PSQI global score.Moreover, 62.6% of the students declared a reduction in social relations and 72.3% an increase in the use of social media during the pandemic period.The majority of respondents reported an extremely severe level of depression (68.1%), anxiety (84.4%) and stress (71.9%).This finding indicate that a relevant percentage of students are poor sleepers with a higher overall PSQI score withdepression and stress and underline the role the implementation of public health interventions to promote healthy life styles and in particular focus on the duration of long night sleep.